The Association Between Air Pollution and Low Birth Weight and Preterm Labor in Ahvaz, Iran - Sarizadeh R; Dastoorpoor M; Goudarzi G; Simbar M (Dove Medical Press, 2020)
Reihaneh Sarizadeh,1 Maryam Dastoorpoor,2 Gholamreza Goudarzi,3 Masoumeh Simbar1 1Midwifery and Reproductive Health Research Center, School of Nursing and Midwifery, Shahid Beheshti University of Medical Science, Tehran, Iran; 2Department of Biostatistics and Epidemiology, Menopause Andropause Research Center, Ahvaz Jundishapur University of Medical Sciences, Ahvaz, Iran; 3Department of Environmental Health Engineering, Air Pollution and Respiratory Diseases Research Center, Ahvaz Jundishapur University of Medical Sciences, Ahvaz, IranCorrespondence: Masoumeh SimbarMidwifery and Reproductive Health Research Center, Department of Midwifery and Reproductive Health, School of Nursing and Midwifery, Shahid Beheshti University of Medical Science, Tehran, IranEmail msimbar@gmail.comPurpose: Pregnant women and fetuses are sensitive to air pollution due to physiological changes in pregnancy. The aim of this study was to determine the relationship between exposure to air pollution, low birth weight and preterm labor in Ahvaz.Methods: This research was a time-series study. The research sample consisted of all data about low birth weight and preterm labor pregnant women from Imam Khomeini Hospital and Razi Hospital in Ahvaz city. Air pollutant data including O3, NO, NO2, SO2, CO, PM10 and PM2.5 and climate data were collected from the Environmental Protection Agency and the Khuzestan Province during a 10-year period from 2008 to 2018. The generalized additive models (GAMs) with different air pollutant lags up to 6 days were used.Results: The results of multiple GAM model have shown that there is a direct and significant relationship between exposure to PM10 at 0– 6-day lag, SO2 at 2- and 3-day lag and low birth weight. In addition, there was a direct and significant correlation between exposure to NO2, NO, CO and PM2.5 at 0– 6-day lag and preterm labor.Conclusion: The results indicate the effect of air pollutants on low birth weight and preterm labor. Therefore, pregnant women should be informed about the negative consequences of air pollution and avoid exposure to polluted air during pregnancy.Keywords: air pollution, low birth weight, preterm labor, Ahvaz, time series